Dispatch for the Industrial Micro-Grid with an Integrated Photovoltaic-Gas-Manufacturing Facility System Considering Carbon Emissions and Operation Costs - Qian Wu; Qiankun Song (Energies)
In this paper, the dispatch for the industrial micro-grid with an integrated photovoltaic-gas-manufacturing facility system considering carbon emissions and operation costs is investigated. Two kinds of energy, electricity and natural gas, are contained in the integer energy system, in which the electricity mainly comes from the PV panels and the utility electricity network, and the natural gas mainly comes from the utility gas network. In addition, electricity and natural gas can be converted into each other. Four kinds of loads, electricity load, gas load, heating load and cooling load, need to be satisfied, in which the electricity load can be divided into fixed load and flexible load. The flexible load comes from the scheduling for manufacturing facilities, and the scheduling of manufacturing facilities is modeled as a kind of deferable load to be integrated into the energy system. Moreover, daily operation costs and carbon emissions are considered in the decision, and the deviation preference strategy is used to solve this multi-objective optimization problem. Finally, a case study with a lithium-ion battery assembly system is proposed. According to the results, it can be found that the proposed model can help managers realize effective scheduling of the industrial micro-grid.